SUSTAINABLE DEVELOPMENT OF TOURISM IN THE REGION THROUGH INCREASING THE COMPETITIVENESS OF TOURIST DESTINATIONS - Atadjanova Shakhnoza Shukhratovna (Labor economics and human capital, 2024)
This article analyzes tourism destinations and destination management processes, providing information on the importance of tourism destinations in the development of tourism in regions and the relevance of their effective management. Recommendations are also offered.